Salvage high‐intensity focused ultrasound for locally recurrent prostate cancer after low‐dose‐rate brachytherapy: oncological and functional outcomes. (2nd July 2019) - Hostiou, Thomas; Gelet, Albert; Chapelon, Jean‐Yves; Rouvière, Olivier; Mège‐Lechevalier, Florence; Lafon, Cyril; Tonoli‐Catez, Hélène; Badet, Lionel; Crouzet, Sébastien
Abstract : Objectives: To evaluate the oncological and functional outcomes of salvage high‐intensity focused ultrasound (S‐HIFU) for locally recurrent prostate cancer after low‐dose‐rate (LDR) brachytherapy. Patients and Methods: Clinical phase II studies (2003–2015) included 50 consecutive patients with post‐brachytherapy local recurrence treated by S‐HIFU. S‐HIFU was performed with post‐external beam radiotherapy (EBRT) parameters and, since 2008, with specific post‐brachytherapy parameters. Treatments were whole‐gland ablation and, since 2009, hemi‐ablation in cases of unilateral prostate cancer. The primary objective was to assess oncological outcomes: treatment failure‐free survival, progression‐free survival (PFS), overall survival (OS), cancer‐specific survival (CSS), and metastasis‐free survival (MFS) rates. The secondary objective was to evaluate adverse events, continence, and erectile function. Kaplan–Meier analysis estimated oncological outcomes. Results: In all, 13 patients were treated with post‐EBRT parameters, 37 with post‐brachytherapy parameters, 35 with whole‐gland treatment, and 15 with hemi‐ablation. The median follow‐up was 4.6 years. After S‐HIFU, the median prostate‐specific antigen level was 0.3 ng/mL. At 6 years, treatment failure‐free survival, PFS, OS, CSS, and MFS rates were 41%, 45%, 93%, 98%, and 80%, respectively. Post‐brachytherapy compared with post‐EBRT parameters reduced Grade 2–3 incontinence (34% vs 62%, P  = 0.015). Incontinence, bladder outlet obstruction and Grade ≥III complications were significantly reduced with hemi‐ablation compared with whole‐gland treatment (14% vs 54%, P  < 0.001; 13% vs 46%, P  = 0.03; 13% vs 63%, P  = 0.001; respectively). Before S‐HIFU, 25 patients had a five‐item version of the International Index of Erectile Function score of ≥17, which was maintained in 48% at 12 months. Conclusion: S‐HIFU for locally recurrent prostate cancer after LDR brachytherapy is associated with favourable survival rates at a price of significant morbidity. Dedicated post‐brachytherapy parameters and hemi‐ablation improve the safety of the treatment.